Strategies of public engagement : shaping a Canadian agenda for international co-operation - Gillies, David, 1952- (McGill-Queen's University Press, 1997)
Given declining budgets and uncertain political support, the environment for international co-operation in Canada and other industrial democracies has become exceptionally challenging. A collection of essays by experts in the field, Strategies of Public Engagement explores ways in which Canadian development organizations and non-governmental organizations (NGOs) can strengthen political and public support.